MiR-129-5p Inactivates NF-κB Pathway to Block Rheumatoid Arthritis Development via Targeting BRD4. (19th April 2022) - Wu, Zhaoli; Chen, Disi
Abstract : Object . Rheumatoid arthritis (RA) is an osteoarticular disease which seriously affects the motor abilities of the patients. MicroRNA disorder has been confirmed as a biomarker event in RA development, and several studies have identified that miR-129-5p is related with the progression of multiple bone diseases. The study attempted to investigate the regulation mechanism of miR-129-5p in RA development. Methods . The abundance of miR-129-5p was detected in the samples including normal tissues and RA tissues and cell lines including human fibroblast-like synoviocytes (hFLSs) and human rheumatoid arthritis fibroblast-like synoviocytes (RA-FLSs). The CCK-8 assay, flow cytometry, Transwell, and ELISA were used to observe the effects of miR-129-5p on the phenotype of RA-FLSs. Moreover, the potential targets of miR-129-5p were identified with TargetScan and dual-luciferase reporter gene assay. Besides, the abundances of the proteins were analyzed with western blot. Results . Decreased miR-129-5p was observed in RA tissues and cells. Increased miR-129-5p obviously blocked the proliferation, inflammatory stress, and migration and remarkably promoted cellular apoptosis. Moreover, BRD4 was confirmed as targets of miR-129-5p, and BRD4 upregulation could partly rescue the inhibition of miR-129-5p on aggressive behaviors of RA-FLSs. Besides, the finding of this study also proved that upregulated miR-129-5p could impede the NF- κ B pathway via targeting BRD4. Conclusion . This study suggests that miR-129-5p suppresses the activation of NF- κ B pathway to block the progression of RA via targeting BRD4.